Carbonaized carbon aerogels derived from pomelo peels for sorption of some organic solvents - Pung, Thitiya; Jitchum, Varangkana; Srisang, Sitthichok; Vichitbandh, Patchanee; Panich-pat, Thanawan (Agriculture and Natural Resources, 2024)
Importance of the work: Agricultural waste materials can be used to fabricate carbon aerogels that can absorb contaminated organic solvents. Objectives: To investigate the potential of pomelo peel carbon aerogel (PCA) as a potential sorbent for organic solvents from the surface of water. Materials & Methods: The peel was removed from pomelo fruits and cut into small pieces, before placing in a freezer at -20°C for 24 hr, followed by freeze-drying at -80 °C for 48 hr and then carbonizing in a muffle furnace at 300°C for 3 hr. Afterward, the carbonized product was characterized for morphology and tested for sorption capacity and reusability. Results: The average density and porosity of the PCA were 0.0777 g/cm3 and 96.12%, respectively. PCA had an interconnected, porous morphology and contained hydrophobic functional groups. The PCA sorption capacities for n-hexane, benzene and toluene floating on the surface of water for 10 s, 20 s and 30 s were in the ranges 5.20–5.96 g/g, 5.34–6.06 g/g and 6.66–7.66 g/g, respectively. The maximum PCA sorption capacities for n-hexane and benzene were at 20 s, while for toluene the maximum sorption capacity was at 10 s. At 20 s, the PCA absorbed more toluene (7.48 ± 0.26 g/g; mean ± SD) than benzene (6.06 ± 0.24 g/g) and n-hexane (5.96 ± 0.16 g/g), respectively. After five cycles of reuse, the PCA sorption capacities for n-hexane, benzene and toluene remained similar to the high values of the initial uptake. Main finding: The PCA, as characterized by water contact angle, the Brunauer-Emmett-Teller specific surface area, field-emission scanning electron microscopy and Fourier transform infrared spectroscopy, had an interconnected, porous morphology and hydrophobic functional groups. PCA expressed good sorption capacity for n-hexane, benzene and toluene floating on surface water and had sustained reusability for five cycles.